1998
DOI: 10.1287/mnsc.44.11.s35
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Driven Quality Improvement

Abstract: Little is known about the processes that make TQM effective. Why are some quality improvement projects more effective than others? We argue that TQM processes affect the way people create new knowledge, which in turn determines organizational effectiveness. We explore this by studying 62 quality improvement projects undertaken in one factory over a decade. Using a factor analysis we identify three learning constructs that characterize the learning process: scope, conceptual learning, and operational learning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(172 citation statements)
references
References 15 publications
13
147
1
6
Order By: Relevance
“…The results are consistent with research conducted by De Geus, 1988;Senge, 1990;Huber, 1991;Dimovski, 1994;Tsang, 1997;Jones & Hendry, 1992;Kezar, 2005;Jones, 2000;Škerlavaj & Dimovski, 2006;Škerlavaj et al, 2007;Liao & Wu, 2009. 3) The results showed that KM affects OP. The results are consistent with research conducted by Škerlavaj & Dimovski, 2006;Wiig, 2002;Gorelick & Monsou, 2005;Liao & Wu, 2009;Darroch, 2005;Alavi & Leidner, 2001;Massey et al, 2002;Schulz & Jobe, 2001;Darroch & McNaughton, 2003;Tanriverdi, 2005;Davenport & Prusak, 1998;Zack, et al, 2009;Mukherjee et al, 1998;Liao & Wu, 2009;Raja Suzana, 2004;2008;Gorelick & Monsou, 2005;Liao & Wu, 2009. …”
Section: Research Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…The results are consistent with research conducted by De Geus, 1988;Senge, 1990;Huber, 1991;Dimovski, 1994;Tsang, 1997;Jones & Hendry, 1992;Kezar, 2005;Jones, 2000;Škerlavaj & Dimovski, 2006;Škerlavaj et al, 2007;Liao & Wu, 2009. 3) The results showed that KM affects OP. The results are consistent with research conducted by Škerlavaj & Dimovski, 2006;Wiig, 2002;Gorelick & Monsou, 2005;Liao & Wu, 2009;Darroch, 2005;Alavi & Leidner, 2001;Massey et al, 2002;Schulz & Jobe, 2001;Darroch & McNaughton, 2003;Tanriverdi, 2005;Davenport & Prusak, 1998;Zack, et al, 2009;Mukherjee et al, 1998;Liao & Wu, 2009;Raja Suzana, 2004;2008;Gorelick & Monsou, 2005;Liao & Wu, 2009. …”
Section: Research Findingssupporting
confidence: 90%
“…One might expect KM to influence many different aspects of OP. KM has been linked positively to financial performance measures (Tanriverdi, 2005) and non-financial performance measures such as quality (Mukherjee et al, 1998). KM makes a difference to OP.…”
Section: The Relationship Between Km and Opmentioning
confidence: 99%
“…This ensures that processes are repeatable, allowing for ongoing incremental improvement, and the realization of benefits of improvement efforts (Hackman & Wageman, 1995;Harrington & Mathers, 1997;Mukherjee, Lapré, & Van Wassenhove, 1998). The ISO 9000…”
Section: Background: the Promise And Reality Of Process Managementmentioning
confidence: 99%
“…As Davenport (1999) show that, although the relationship between KM and performance indicators has been discussed at length of balance sheet, exchange value, market value, etc, few firms have been able to create a causal relationship between KM activities and OP utilising traditional measurements. Many scholars have therefore felt it necessary to attempt to measure other OP indicators when attempting to investigate the effects of KM including non-financial performance measures such as productivity (Lapre and Wassenhove, 2001), quality (Mukherjee, Lapre, and Wassenhove, 1998), and innovation (Francisco and Guadamillas, 2002). Cotora (2007) claimed that to measure corporate performance, it is imperative that a system takes into account indefinable values such as competencies, partnerships and knowledge along with inter-relationships and the process of conversion in situations.…”
Section: Organisational Performancementioning
confidence: 99%